(untitled) (Journal of Dhaka National Medical College & Hospital, 2016)
Background & Aims: A major portion of urinary tract infections are caused by Escherichia coli. It has been found that these organisms are being increasingly resistant to broad spectrum B- lactam antibiotics mediated by extended Spectrum B-lactamase (ESBL) enzymes. The present study was undertaken to determine the antimicrobial susceptibility pattern and the incidence of ESBL production among Escherichia coli strains isolated from urine. Materials & Methods: Urine specimens from patients were subjected to culture as per Clinical Laboratory Standard Institute (CLSI) guidelines. All specimens were inoculated on to Blood agar and MacConkey agar plates and growth showing significant bacteriuria (>105 colony/ml of urine) were further identified by the standard biochemical procedures. Detection of ESBL production by isolated E.coli strains was done by Double Disc Synergy Test which is a phenotypic confirmatory test for ESBL production. Antibiotic susceptibility testing of isolates was also done as per CLSI guidelines. The study was conducted from 1st January, 2014 to 30th June, 2015. Result: A total of 377 E.coli strains were isolated of which 165 (44%) isolates were ESBL producers. Susceptibility pattern of isolates to Ceftriaxone, Ceftazidime, Cefixime and Ciprofloxacin was not satisfactory. More than 80% sensitivity was found only to Imipenem (96%), Nitrofurantoin (91%) and Amikacin (89%). Conclusion: The presence of ESBL carries tremendous clinical significance. As the ESBLS are frequently plasmid encoded & same plasmid can carry genes encoding resistance to other antibiotic group, thus extremely limiting the antibiotic treatment option J. Dhaka National Med. Coll. Hos. 2016; 22 (01): 33-36